SOSIALISASI PELAYANAN PRIMA DAN PENGEMBANGAN HOMESTAY BAGI MASYARAKAT DI DESA WISATA TAJEN, KECAMATAN PENEBEL, KABUPATEN TABANAN - Adi, Ida Ayu Sri Puspa; Indrayani, I Gusti Ayu Putu Wita; Darmaputra, Putu Gede Eka; Sekarti, Ni Ketut; Pitanatri, Made Uttari (Jurnal Pengabdian Kepada Masyarakat Makardhi, 2025)
Tajen Tourism Village is a pioneering tourist village that already has various tourism potentials that are ready to be developed. As for the choice to carry out outreach to the community in the Tajen Tourism Village, it is for various reasons, including the village's potential, there are already a lot of tourists visiting and even staying overnight, there are still a few existing homestays and the tourist village is ready to develop homestays according to tourists' expectations. However, judging from the existing potential, the village community has not been able to provide maximum service to tourist requests, both in terms of service when providing culinary delights and homestay cleaning services. For this reason, this community service is carried out in the form of Socialization of Tourism Village Services, with participants from all stakeholders in the Tajen Penebel Tourism Village. The output of this community service activity is to increase the community's understanding of excellent service to tourists, increase the understanding of the meaning of homestay, increase the community's ability to clean and clean homestays, and increase the community's readiness to receive both domestic and international tourists.